Work Resumption Rate and Migrant Workers' Income During the COVID-19 Pandemic - Li, Jiaxiang; Chu, Baoju; Chai, Nana; Wu, Bi; Shi, Baofeng; Ou, Feiya (Frontiers in Public Health, 2021)
The COVID-19 public health crisis has led quickly to an economic crisis, impact on many people and businesses in the world. This study examines how does pandemic affects workforces and workers’ income. We quantify the impact of staggered resumption of work, after the coronavirus lockdowns, on the migrant workers’ income. Using data on population movements of 366 Chinese cities at the daily level from the Baidu Maps -Migration Big Data Platform and historical data on the average monthly income of migrant workers, we find that the average work resumption rate (WRR) during the period of the Chinese Lantern Festival was 25.25% which was only 30.67% of that in the same matched lunar calendar period in 2019. We then apply Grey Model First Order One Variable [GM (1, 1)] to predict the monthly income of migrant workers during the period of the COVID-19 pandemic. We show that if without the influence of the COVID-19 pandemic the average monthly income of migrant workers in 2020 will be expected to increase by 12% compared with 2019. We further conduct scenario analysis and show that the average monthly income of migrant workers in 2020 under the conservative scenario (COS), medium scenario (MES) and worse scenario (WOS) will be predicted to decrease by 2%, 21% and 44%, respectively. Through testing, our prediction error is less than 5%. Our findings will help policymakers to decide when and how they implement a plan to ease the coronavirus lockdown and related financial support policies.